Unlocking Africa's climate ambition: Assessing NDC 3.0, NAPs, and LT-LEDS: A review report - Mundia, Carolyne; Njuguna, Lucy; Akoko, Tessie; Chilambe, Pedro (2025)
Africa faces disproportionate vulnerability to climate change, with intensifying hazards threatening its agriculture, water security, and development. In response, countries are developing key policy instruments under the Paris Agreement: updated Nationally Determined Contributions (NDC 3.0s), National Adaptation Plans (NAPs), and Long-Term Strategies (LT-LEDS). This paper provides a systematic review of these submissions from African nations following the first Global Stocktake. It assesses their ambition, technical robustness, and alignment with global goals, identifying persistent gaps in finance, data, and capacity. The analysis aims to clarify current progress, highlight critical challenges, and inform targeted support to enhance the implementation and effectiveness of Africa’s climate action.